2022
DOI: 10.1111/1462-2920.16086
|View full text |Cite
|
Sign up to set email alerts
|

Rapid changes in coastal ocean microbiomes uncoupled with shifts in environmental variables

Abstract: Summary Disturbances, here defined as events that directly alter microbial community composition, are commonly studied in host‐associated and engineered systems. In spite of global change both altering environmental averages and increasing extreme events, there has been relatively little research into the causes, persistence and population‐level impacts of disturbance in the dynamic coastal ocean. Here, we utilize 3 years of observations from a coastal time series to identify disturbances based on the largest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…However, more than half of these populations returned to rarity one or two weeks after each disturbance, consistent with the concept of conditionally rare taxa (CRT) defined by Shade and colleagues [7] and also the results of amplicon based analysis of same samples [22]. Such conditionally rare taxa may therefore provide resilience to the system undergoing disturbances and our approach here quantified this contribution in terms of relative abundance of the total community.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…However, more than half of these populations returned to rarity one or two weeks after each disturbance, consistent with the concept of conditionally rare taxa (CRT) defined by Shade and colleagues [7] and also the results of amplicon based analysis of same samples [22]. Such conditionally rare taxa may therefore provide resilience to the system undergoing disturbances and our approach here quantified this contribution in terms of relative abundance of the total community.…”
Section: Discussionsupporting
confidence: 77%
“…These results suggested that there were more carbon compounds in the surface seawater during this warming event compared to pre-disturbance sample, and microbial populations that were more efficient in utilizing those carbon gained a competitive advantage over those that lacked these pathways (e.g., abundant to rare MAGs). Amplicon based analysis also showed consistent results: a “spring bloom” indicating overturn in the phytoplankton was obvious based on the amplicon datasets [22]. However, two weeks after the event, 14 of the MAGs that had become abundant from rare during the event became rare again (77.8% of the category) while 11 MAGs that became rare from abundant became abundant again (66.7% of the category), revealing that the sampled microbial communities were resilient.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Similarly, microbiomes from stable environments may be more sensitive to environmental changes [9,10]. However, in aquatic ecosystems, establishing antecedent environmental conditions is particularly challenging due to factors including water movement, unmeasured disturbances and environmental parameter seasonality [11][12][13]. Further, although dispersal limitation is assumed be reduced in aquatic systems compared to other systems, such as soils, oceanographic features such as steep frontal gradients between water parcels or vertical stratification can limit dispersal [14], and thus constrain microbiome composition [15].…”
Section: Introductionmentioning
confidence: 99%